Assessing the impact of the Agriculture Perspective Plan (1995 to 2015): The maoist insurgency on rural lives in Nepal and reflections on the current Agricultural Development Strategy - Cameron, John; Pandey, Phaindra; Kafle Wagle, Bimala (New Angle: Nepal Journal of Social Science and Public Policy, 2016)
The fifteen years between 2053 and 2072 in the Nepalese calendar (approximately 1996 to 2015 in the Gregorian calendar) were potentially dramatic for rural development in Nepal. A twenty year market oriented, Asian Development Bank funded and technically assisted, national Agriculture Perspective Plan (APP) was in the early stage of implementation and a Maoist movement was about to launch an armed struggle in rural area that would become a national civil war lasting ten years. The APP had envisioned agriculture intensification for agriculture based economic growth adequate to generate employment to combat poverty in Nepal. The comparison of two Nepal Living Standards Surveys (NLSS) results from 1995/96 and 2010/11 suggests that agricultural production has not changed substantially in the topographically advantaged west rural plains (terai) areas, where the Maoist insurgency had relatively small direct influence. Overall, the Nepalese economy appears to be both moving away from agriculture (share of non-farm income rising from 15% to almost 40%) and feminising (women headed households in the rural western terai rising from under 9% to over 24%). However, over fifteen years there have been significant changes in the livelihood patterns of different caste/ethnic/religious groups. This paper deals with identified five different types of changed behaviour to show the range of responses and links are made to misrecognised key elements in political economy of Nepal, the Maoist insurgency and the Nepal State conflict.